Effects of harvesting mediated by dispersal traits. (3rd May 2018) - Cantrell, R. S.; Cosner, C.
Abstract : Abstract: Trait‐mediated behavioral responses to other species, especially predators, can have important effects on the dynamics of populations. One effect is to modify dispersal patterns, which in turn can modify population dynamics and species interactions. We model a situation where a focal population responds to disturbances created by the harvesting of another population by increasing the rate of random dispersal by individuals. The model shows that in some situations this effect can result in the extinction of the focal population, even if it is not itself subject to harvesting. This observation suggests that it may be desirable to consider trait‐mediated effects when assessing the possible impacts of harvesting on conservation. Recommendations for Resource Managers: Be aware that harvesting a given crop or population can affect other populations because of their behavioral responses to the harvesting activity, even if it does not directly impose mortality on those populations or change their interactions with other species. A way that harvesting activity can affect nonharvested populations is to increase their dispersal rate. Managers should be aware that this has the potential to cause extinction in some situations even if no other effects of harvesting are present. For some populations, harvesting resources with which they interact or share an environment could in principle cause both direct and indirect effects, which could combine to have a different, perhaps greater, impact than either one would have separately.